Pengendalian Kualitas Produk dengan Metode Six Sigma, Seven Tools, dan Kaizen untuk Mengurangi Produk Cacat di PT. Mitra Rekatama Mandiri - Petrus Wisnubroto; Marcelino Yogi (Program Studi Teknik Industri Universitas Setia Budi, 2016)
PT. Mitra Rekatama Mandiri is one of the manufacturing industries engaged in metal casting and machining which manages and produces metal castings, with output in the form of components of agricultural equipment and mining, which is the pulley. The work carried out by machine and manually. The production process is still a lot of damage to products that are not suitable quality standards set by the industry. Therefore, to identify, analyze and repair the damage factor products used in the production process quality control methods, by Six Sigma and seven tools and Kaizen. Based on the research results in the form of data processing and analysis with DMAI cycle in the concept of Six Sigma DMAIC define phase characterizing the quality (CTQ) attribute data in the form of as many as 10 different types of damage. The results of the identification process to map control measure p on stage. The results of the baseline measurements of corporate performance in the production process of finishing obtained DPMO value of 88.716 which may mean that a million chance there will be 88.716. Producted possibility of the product damage. Finishing the production process is at 3:57 sigma level. The result of identification with Pareto diagram and with CTQ most dominant cause damage that is kind rantap of 98% followed by the kind of broken mengsle 94%, 78% kropos kind of broken, damaged type of lump 46% of the total to be damaged by 265. identify problems damage with fish bone diagram to determine the factors that cause the damage. In the improve phase seek corrective action plan with Kaizen Kaizen implementation of two instruments, namely Five M Check List and Five Step Plan. From the analysis, it can be concluded that the main cause of damage is the human factor and the environment, and as well as Kaizen implementation tools’, the main policy that must be executed by the management company that surveillance or tighter control every stage of the process. Improvement by analyzing the factors that cause defective products made to reduce the most dominant types of damaged, so that product quality is maintained according to customer demand. Keywords: defect, Kaizen, quality control, seven tools, six sigma